Pengaruh Instagram Terhadap Tingkat Kepercayaan Bergaul Mahasiswa (Faculty of Communications Science, Dr. Soetomo University, 2019)
Instagram is one of the most popular social networking sites and is accessed every day by STIKOM InterStudi students. No wonder that almost everyone especially teenagers have Instagram accounts. Student confidence is open in the same characteristics so they can get along. Instagram is currently a social media that is on the rise with active users monthly reaching 1 billion users with an increase of around 200 million from 2017 and ranks fourth most used social media in Indonesia after YouTube. In this study a quantitativeapproach is used, basically the quantitative approach is carried out in inferential research and makes conclusions about the results of a probability of rejection of the null hypothesis null. Population is an object / subject area that has certain characteristics, the area to be 66 taken is InterStudi STIKOM students to draw their conclusions. The primary data used in this study was a questionnaire conducted by giving a set of questions or written statements to respondents to answer. Respondents can give answers in the range of positive to negative answers. Respondents who give an assessment number with number 9, mean respondent's perception of the leader was very positive, whereas if the give answered in number 5, itmeant neutral, and if the give answered in number 1, the respondent's perception of the leader was very negative. Keywords: Level of Confedence, Collage Student, Instagram, Characteristics, Communication.